Solve the system of equations using substitution.
y = x + 6
y = –2x – 3
5 answers
http://www.jiskha.com/display.cgi?id=1356132049
I still trying to do it, but it is hard for me, can you explain that again?
Thanks Ms. Sue.
Thanks Ms. Sue.
y = x + 6
y =
Obviously y is the same in both equations.
x + 6 = –2x – 3
Combine like terms.
3x = -3 - 6
3x = -9
x = -3
y = -3 + 6
y = -3
y =
Obviously y is the same in both equations.
x + 6 = –2x – 3
Combine like terms.
3x = -3 - 6
3x = -9
x = -3
y = -3 + 6
y = -3
Thanks, now i got it :)
You're welcome. :-)